Penggunaan Media Canva Edu Interaktif Untuk Meningkatkan Keterampilan Menyimak Teks Deskriptif Pada Siswa Kelas VI Sdn 2 Sedayu Tulung Klaten - Dwi Nursakti Prihatinningsih; Basuki .; Nanik Herawati; Hersulastuti . (CV. ITTC INDONESIA, 2025)
The rapid development of technology demands teachers to be creative and innovative in the learning process. Optimal use of technology-based learning media is an effective strategy to improve the quality of learning and student engagement. This study aims to improve descriptive text listening skills through the use of interactive Canva Edu media in sixth-grade students of SD Negeri 2 Sedayu in the 2025/2026 academic year. This study uses a Classroom Action Research (CAR) approach which is implemented in two cycles, each consisting of planning, implementation, observation, and reflection stages. The research subjects were 15 students. Data collection techniques were carried out through observation, learning achievement tests, student response questionnaires, and documentation. Data analysis used qualitative analysis of the Miles and Huberman model and quantitative analysis to calculate the average and percentage of learning completeness. The results of the study showed an increase in student activity and learning outcomes. In the first cycle, the average score was 66.17 with learning completeness of 20%, while in the second cycle the average score increased to 90.37 with learning completeness reaching 93.33%. Thus, the use of interactive Canva Edu media has proven effective in improving the listening skills of descriptive texts of grade VI students at SD Negeri 2 Sedayu.